Testing Numeric: Evidence from a randomized controlled trial of a computer based mathematics intervention in Cape Town high schools - Böhmer, Bianca (School of Economics, 2016)
This thesis presents the results of randomized controlled trial conducted to evaluate a Grade 8 after-school mathematics intervention. The programme employed student coaches to facilitate classes in which Khan Academy resources were used to teach basic numeracy. Large gains of 0.321 standard deviations were observed on basic numeracy outcomes for learners who were selected to be on the programme. Similarly, learners in treatment also scored 0.246 standard deviations higher on core Grade 8 curriculum questions at endline. The improvements in mathematics outcomes were evident for learners throughout the distribution and treatment learners outperformed control group learners on every subsection of the mathematics test. There was also no significant differential treatment effect by gender, race, home language, baseline typing speed or cognitive development. However, treatment learners with better English literacy at baseline scored significantly higher than learners in the bottom third on core grade 8 curriculum questions. Additionally, despite close contact between control and treatment learners, no statistically significant evidence of spillover was detected.